2014
DOI: 10.1177/1367006914534330
|View full text |Cite
|
Sign up to set email alerts
|

Narrative abilities in subgroups of English language learners and monolingual peers

Abstract: Aims and objectives: The objective of this study was to examine the narrative ability of two subgroups of English Language Learners (ELLs) relative to a group of English monolingual (EL1) peers. Specifically, we investigated whether the three groups of children differed on measures of narrative macrostructure and microstructure. Methodology: Two groups of ELLs were identified on the basis of parent report of the language most often heard and spoken at home (ELL English language users, ELL minority language use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 41 publications
8
41
0
1
Order By: Relevance
“…A recent study by Hipfner‐Boucher et al . () with a narrative retell task confirms this conclusion. Two groups of children who learned English as their L2 were compared with a group of monolingual English children on narrative macro‐ and micro‐structure.…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…A recent study by Hipfner‐Boucher et al . () with a narrative retell task confirms this conclusion. Two groups of children who learned English as their L2 were compared with a group of monolingual English children on narrative macro‐ and micro‐structure.…”
Section: Introductionsupporting
confidence: 71%
“…That is, cross-language correlations were found for measures of narrative macro-structure, whereas this was typically not the case for micro-level variables (Pearson 2002, Squires et al 2014, Uccelli and Páez 2007. Studies that have compared mono-and bilingual children's narrative performance also find differences between macro-and micro-structure (Hipfner-Boucher et al 2015, Pearson 2002. Pearson (2002) used a story generation task and found that monolingual English children outperformed their bilingual Spanish-English peers on measures of micro-structure.…”
Section: Narrative Performance Of Bilingual Childrenmentioning
confidence: 99%
See 3 more Smart Citations